Towards A Post-Traumatic Urban Design That Heals Cities’ Inhabitants Suffering From PTSD - Maria A EL Helou (Journal of Contemporary Urban Affairs, 2020)
Cities are generally in a state of constant modification. Some experience this modification at a more rapid pace due to the technology available in the city; others experience this modification due to the city’s time of life, which requires many civilizations to imprint their architectural style and project their social image and identity. In certain cases, these modifications are due to natural disasters, such as earthquakes or tsunamis, or man-made wars, or even both. The study revealed that the relationship found between the ability of “Beirutis” (how Beirut’s original inhabitants call themselves) to perceive their identity through the built environment and PTSD, will help urban planners and architects find the procedures based on observation and scientific facts to build with the opportunity to heal disaster-torn cities’ inhabitants from PTSD